Digital technologies: holy grail in India's quest for financial inclusion? - Duvvuri Subbarao (2023)
India struggled for decades with the challenge of financial inclusion – providing low-income households the opportunities of the formal financial sector. But it proved to be an uphill task. That was until digital technologies opened up exciting possibilities over the last ten years. This revolution has yet to run its course.